Blood antioxidant nutrients in riparian villagers of the Brazilian Amazon: its associations with wet/dry seasons and modulation by sociodemographic determinants - Juliana Valentini; Carlos José Sousa Passos; Solange Cristina Garcia; Robert Davidson; Marc Lucotte; Frédéric Mertens; Christine Romana; Lígia Meres Valadão; Mariele Feiffer Charão; Marília Baierle; Fernando Barbosa Júnior (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2016)
Abstract This study associates blood antioxidants like copper (Cu), manganese (Mn), selenium (Se), zinc (Zn), β-carotene, lycopene and vitamins (A and E) to sociodemographic features and seasonality in communities from the Tapajós River region, Brazilian Amazon. We observed increased Mn, Se and Zn levels compared to the average Brazilian population, whereas this is only the case for β-carotene in the rainy season. Lycopene levels fall within the reference range, although lower than those found in other Brazilian regions. Cu, Se, Zn, β-carotene, lycopene and vitamin E levels vary among seasons. β-carotene, Mn and Se vary among communities. Se and Zn vary with smoking habits and sex, respectively. In addition, β-carotene and vitamins (A and E) are altered by alcohol consumption. Villagers who both farmed and fished present higher Cu and lower β-carotene levels than participants with a single occupation. Vitamin E levels depend upon the individual state of origin. These data provide important baseline information for antioxidant status in this Amazonian riparian population.